Coordination, Surveillance and Administrative Responsibility of the Parent Company in Safety and Health at Work - Lengua Apolaya, César (2016)
This article analyzes the essential obligations arising on safety and health at work with regard to the parent company in a scheme of productive decentralization, which is characterized in our midst by the widespread use of labor intermediation and outsourcing services both modalities recognized and regulated by Peruvian law.